Community Empowerment: Hydroponic Cultivation in Pepelegi Village - mariyati, lely ika; Utami, Mulya Isti; Sari, Risa Indah; Lutfiyah, Siti Aisyah (Mujtama Jurnal Pengabdian Masyarakat, 2023)
The problem of limited space in urban areas makes fertile agricultural land insufficient. Hydroponic empowerment in the Aisyiyah organization of Pepelegi Village aims to face and take advantage of existing opportunities, with the hope of increasing the prosperity of the village communities, and providing sustainable solutions in agriculture in Pepelegi Village, Waru District, Sidoarjo Regency. The method used is a community approach, socialization and training, mentoring, monitoring and evaluation, and community involvement. The implementation of this hydroponic empowerment provides great benefits as indicated by the success of planting vegetables using a simple hydroponic system that can be applied by the Aisyiyah Pepelegi Village branch administrator in the household scope.